2023
DOI: 10.1111/jar.13104
|View full text |Cite
|
Sign up to set email alerts
|

Preventing falls at home among people with intellectual disabilities: A scoping review

Abstract: Background Falls are common among people with intellectual disabilities. Many falls happen within the home. Our scoping review aimed to identify evidence for falls‐risk factors and falls‐prevention interventions for this population. Method We conducted a multi‐database search to identify any type of published study that explored falls‐risk factors or falls‐prevention interventions for people with intellectual disabilities. Following a process of (i) title & abstract and (ii) full‐text screening, data was extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Environmental factors relating to falls risks were highlighted as important to consider within the programme and a recent scoping review of risk factors for falls for AWID reported falls were most likely within the home environment and often in bathrooms, toilets and bedrooms. 17 Concerns were, however, expressed by some AWID about navigating obstacles in new environments and this could potentially lead to a reduced confidence in going out. The implications of not going out could include social isolation as well as reduced independence, mobility and the ability to carry out daily tasks.…”
Section: Open Accessmentioning
confidence: 99%
“…Environmental factors relating to falls risks were highlighted as important to consider within the programme and a recent scoping review of risk factors for falls for AWID reported falls were most likely within the home environment and often in bathrooms, toilets and bedrooms. 17 Concerns were, however, expressed by some AWID about navigating obstacles in new environments and this could potentially lead to a reduced confidence in going out. The implications of not going out could include social isolation as well as reduced independence, mobility and the ability to carry out daily tasks.…”
Section: Open Accessmentioning
confidence: 99%